Under the Dual Carbon Goal, Explore a Climate Change Litigation Model Suitable for China - Liang, Yinglin (International Journal of Social Sciences and Public Administration, 2024)
Climate change is a huge global challenge, in the past few decades, the average temperature of the earth has gradually increased, carbon dioxide is the main gas causing the temperature to rise, so reducing carbon emissions is an important measure to combat climate change. March, 2021,the Outline of the 14th Five-Year Plan (2021-2025) for National Economic and Social Development and the Long-Range Objectives Through the Year 2035, adopted on March 11 at the annual session of China's top legislature, has been published in a booklet adopted at the Fourth Session of the 13th National People's Congress,it shows that China has officially put forward the "dual carbon" goal from the national policy level, which reflects China's responsibility as a major country in climate change and its determination to govern. The academic community attaches great importance to the "dual carbon" goal, but because the "double carbon" goal has been proposed for a short time, the legal system is still not perfect, and there is a situation of "policy is popular while law is unpopular" in China. This paper, utilizing both the normative analysis method and the case analysis method demonstrate the difficulties existing in judicial practice, such as the slow progress of climate change litigation in China, the lack of a complete system, the difficulty in arguing the causal relationship, and the lack of clarity in the way of responsibility. In view of the prevailing circumstances surrounding climate change and the realm of public interest litigation pertaining this critical issue, I would like to put forward a series of suggestions, aiming to provide solid support for the country to formulate a more comprehensive and effective climate change policy and legal framework through in-depth exploration of judicial practice. These recommendations focus not only on improving litigation mechanisms, but also on sensitizing the justice system to environmental issues, so as to ensure that the law can more precisely serve the urgent needs of climate change governance.